2016
DOI: 10.1039/c5nj02816g
|View full text |Cite
|
Sign up to set email alerts
|

SBA-15 functionalised with high loading of amino or carboxylate groups as selective adsorbent for enhanced removal of toxic dyes from aqueous solution

Abstract: Amino- or carboxylate-functionalised SBA-15 acts as a selective adsorbent and shows enhanced adsorption capacity for toxic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 66 publications
0
60
0
2
Order By: Relevance
“…The adsorption experiments at varying temperatures (303, 308, and 313 K) were carried out to estimate the influence of temperature on dyes uptake ( Figure 10). Although these temperatures are very close, but many adsorption studies at close temperature intervals have been reported which provide satisfactory results of thermodynamic parameters [51][52][53][54]. Percent removal of MV increased from 91.92 to 92.52, while that for MG from 93.66 to 94.60 suggesting that adsorption was more favored at higher temperature.…”
Section: Effect Of Temperaturementioning
confidence: 95%
“…The adsorption experiments at varying temperatures (303, 308, and 313 K) were carried out to estimate the influence of temperature on dyes uptake ( Figure 10). Although these temperatures are very close, but many adsorption studies at close temperature intervals have been reported which provide satisfactory results of thermodynamic parameters [51][52][53][54]. Percent removal of MV increased from 91.92 to 92.52, while that for MG from 93.66 to 94.60 suggesting that adsorption was more favored at higher temperature.…”
Section: Effect Of Temperaturementioning
confidence: 95%
“…Furthermore, the amount of functional groups graed on the SBA-15 surface was conrmed by elemental analysis. 30,35 The chemical and physical properties of the SBA-15 samples are presented in Table 1. 3.2 Adsorption study 3.2.1 Effect of the initial pH. The effects of initial pH on the dye adsorption by SBA-15-BOP were studied in 50 mL polyethylene tubes containing 30 mL of 200 mg L À1 CR dye or 100 mg L À1 RR2 dye solutions with 10 mg of adsorbent at 25 C for 60 min by varying the initial pH of the solution from 3.0 to 9.0 (Fig.…”
Section: Characterization Of the Adsorbentmentioning
confidence: 99%
“…[27][28][29][30] For instance, many reports related to the application of SBA-15 in the recovery of uranium(VI) [29][30][31][32] are available; moreover, the functionalized SBA-15 materials have also been found to efficiently remove various dyes such as methyl orange, reactive blue, methylene blue and acid blue, 27,28 while there are some limitations to their application. [23][24][25][26][27][28][29][30][31][32][33][34][35] Phosphonic-based ligands form the most important ligand family, which have numerous interesting chemical structures such as phosphates, phosphonates or organophosphorus derivatives. [36][37][38] These ligands exhibit remarkable coordination abilities and high chemical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Both kinds of polyelectrolytes can be utilized in water and wastewater treatment. According to studies, it seems that many chemical molecules, such as amino, [34] poly diallyldimethylammonium chloride, [35] chitosan, and pyridine [36] can provide useful functional groups to adsorbed dye contaminates. As a reported adsorbent, chitosan (CTS) is extensively applied for removing environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%